Biochemical Efficacy and Safety of a New, Ready-to-Use, Liquid Alpha-1-Proteinase Inhibitor, GLASSIA (Alpha1-Proteinase Inhibitor (Human), Intravenous). (1st February 2014) - Sandhaus, Robert A.; Stocks, James; Rouhani, Farshid N.; Brantly, Mark; Strauss, Pnina
Abstract: Maintaining serum levels of alpha-1-proteinase inhibitor (A1PI) >11 μM by augmentation with plasma-derived human A1PI is currently the only specific therapy available to treat patients with the genetic deficiency of A1PI. In this study, a new, high-purity (≥90% A1PI in monomeric form), ready-to-use, liquid formulation of A1PI—GLASSIA (Kamada, Ness Ziona, Israel) was compared to PROLASTINÆ (Talecris, Research Triangle Park, NC, now Grifols), both commercially available, FDA-approved products. This multicenter, double-blind, randomized controlled trial with partial cross-over was designed to test the non-inferiority and safety of GLASSIA compared to PROLASTIN, assessing both antigenic and functional A1PI trough levels in subject serum. Non-inferiority of GLASSIA to PROLASTIN was demonstrated by remaining within the lower bounds of the confidence intervals (≤3 μM) for both antigenic and functional A1PI. The study concluded that GLASSIA, a new liquid, ready to use, formulation of A1PI, was not inferior to PROLASTIN and it was well tolerated with a safety profile comparable to PROLASTIN.